Nature and Quality of Interactions Between Elementary School Children Using Video-Modeling and Peer-to-Peer Evaluation With and Without Structured Video Feedback - San, Nick Caung; Lee, Hyun Suk; Bucholtz, Victoria; Fung, Tak; Rafiei Milajerdi, Homa; Katz, Larry (Frontiers in Education, 2022)
The purpose of this study was to examine the nature and quality of interactions between 24 students (9 male, 15 female) in an Alberta elementary physical education class using video-modeling and three different peer-to-peer (P2P) evaluation methods. Nature of interaction was determined by the duration of interaction (total, on-task time, off-task time, neutral), the type of comments (positive, constructive, negative), and quality of interaction by the category of feedback (4 categories) from both the evaluators and performers. This study compared structured paper evaluation (SP), unstructured video evaluation using the video feature on iPads (UV), and structured video evaluation using a prototype app on the iPad (SV). The SV condition provided statistically significant results for evaluator on-task, evaluator off-task, and performer on-task, along with increased positive comments from evaluators. The SP condition had significantly more depth of feedback. This study concludes that the use of SV to deliver feedback in a P2P learning environment has the potential to improve the nature of feedback during peer evaluations.